Formedness of Informational-Cognitive Component of Health Culture of the Future Teachers of Physical Culture and the Ways of its Improvement - Moseichuk , Yurii; Мihai-RaduJacob; Moroz, Olena (Pedagogical Discourse, 2019)
During the professional training of the future teachers of physical culture in higher education institutions it is necessary to form an appropriate level of health culture. It will give a possibility for the future teachers to competently carry out their professional activities, be an example for the pursuit of health. We consider components as the most significant parts of the culture of health, which fully reflect its content and characterize its features. The health culture is considered through the unity and interrelation between the motivational-value, informative-cognitive, organizational-activity, personal-emotional and reflexive-evaluation components. The article presents a thorough description of the informational-cognitive component of the health culture of the future teachers of physical culture. The results of monitoring on the formation of indicators (completeness of knowledge about the culture of health and the level of general outlook) of this component at the research stage have been described. The completeness of knowledge about the culture of health has been tested on the basis of two methods –comprehensive survey and methodology «Unfinished sentences». Written work allowed covering all areas of activity of the future teachers of physical culture. The object of evaluation was a set of acquired knowledge, a formed system of professional competencies. Monitoring has shown that the health culture of students is spontaneous, and therefore only one fifth of respondents has a high (creative) level, while 2/3 of respondents have an average (basic) level. The main focus is on highlighting practical mechanisms for improving the informational-cognitive component of health culture through interdisciplinary integration of knowledge. It is advisable to carry out the rapprochement of related disciplines, due to their convergence. We should implement the integration of compulsory examination and postgraduate disciplines in the bachelor’s degree and the subjects of professional and practical training in the undergraduate and magistracy. Based on the principles of interdisciplinary integration, it is advisable to coordinate the curricula of teaching disciplines in order to avoid repetitions, as well as to substantially improve the methodological support.